Adobe Animate classroom in a book (2022 release) - Chun, Russell (AdobePress, 2022)
The 2022 release of Adobe Animate provides significant new controls for animation with puppet warping and improvements to layer parenting, and enhancements to paint brush preferences and symbol options. Learn to use the revamped Asset Warp tool for a modern rigging approach to animating shapes and bitmap images. Work with a more robust set of playback options for graphic symbols that provides total control over looping. Quickly publish to social media channels with support for SVG, WebGL, HTML5, animated GIFs, and HD video. Seamless collaboration through Adobe Creative Cloud makes Adobe Animate the ideal development environment for creative animation and multimedia. The fastest, easiest, most comprehensive way to learn Adobe Animate Classroom in a Book®, the best-selling series of hands-on software training workbooks, offers what no other book or training program doesan official training series from Adobe, developed with the support of Adobe product experts. Adobe Animate Classroom in a Book (2022 release) contains 11 lessons that cover the basics and beyond, providing countless tips and techniques to help you become more productive with the program. You can follow the book from start to finish or choose only those lessons that interest you. Purchasing this book includes valuable online extras. Follow the instructions in the book's "Getting Started" section to unlock access to: Downloadable lesson files you need to work through the projects in the book Web Edition containing the complete text of the book, interactive quizzes, and videos that walk you through the lessons step by step What you need to use this book: Adobe Animate (2022 release) software, for either Windows or macOS. (Software not included.) Note: Classroom in a Book does not replace the documentation, support, updates, or any other benefits of being a registered owner of Adobe Animate software.